Analisis Kelayakan Usaha Pada Keripik Nangka UMKM Sang Bintang Kabupaten Ketapang - Indriawan, Rois (Politeknik Negeri Ketapang, 2023)
This research was conducted to evaluate the income level and feasibility of the micro, small, and medium enterprise (UMKM)